2007
DOI: 10.1002/chin.200744119
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Evaluation of Some New Thiazole, Thiazolidinone and Thiazoline Derivatives Starting from 1‐Chloro‐3,4‐dihydronaphthalene‐2‐carboxaldehyde.

Abstract: A series of title compounds is prepared and tested for antimicrobial effects. Derivatives such as (XIb), (XV), and (XVII) show high activities. -(BONDOCK*, S.; KHALIFA, W.; FADDA, A. A.; Eur. J. Med. Chem. 42 (2007) 7, 948-954; Dep. Chem., Fac. Sci., Mansoura Univ., Mansoura 35516, Egypt; Eng.) -M. Bohle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Therefore, a dual COX inhibitory-antibacterial agent with an improved safety profile is necessary for enhanced therapeutic benefits and better patient compliance. Prompted from this requirement lot of studies have been reported [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] . As a result, above-mentioned information directed us to synthesize some novel 2-(4-substitutedmethylphenyl)propionic acid derivatives and investigate their inhibitory activity against COX-1, COX-2 enzymes and various microbial strains.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a dual COX inhibitory-antibacterial agent with an improved safety profile is necessary for enhanced therapeutic benefits and better patient compliance. Prompted from this requirement lot of studies have been reported [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] . As a result, above-mentioned information directed us to synthesize some novel 2-(4-substitutedmethylphenyl)propionic acid derivatives and investigate their inhibitory activity against COX-1, COX-2 enzymes and various microbial strains.…”
Section: Introductionmentioning
confidence: 99%
“…They are also useful as anti-allergic 13 , anti-inflammatory 14 and anthelmintic 15 agents and as appetite depressants 16 , intermediates for dyes 17 , plant protectants 18 , histamine H2antagonists 19 and photographic sensitizers 20 . On the other hand, careful literature survey revealed that thiazole, thiophene and pyrazole ring systems have occupied a unique position in the design and synthesis of novel biological active agents with remarkable analgesic and antiinflammatory activities [21][22][23] , in addition to their well documented potential antimicrobial activities [24][25][26][27] . Morever, thiazoles have found application in drug development for the treatment of hypertension 28 , schizophrenia 29 , HIV infections 30 , and as new inhibitors of bacterial DNA gyrase B 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Trimethoprim, the dihydrofolate reductase inhibitor, is used in combination with sulfa drugs to increase the therapeutic efficacy 19 . On the other hand, 2,3-dihydrothiazoles and 4-thiazolidinones have occupied a unique position in the design and synthesis of biologically active antimicrobial agents [20][21][22] . In this study, we used the reported STZ-DHPP adduct 18 as a lead compound to design potent antimicrobial agents targeting both the PABA and pterin-binding pockets of the DHPS enzyme, thereby inhibiting the biosynthesis of the dihydrofolic acid.…”
Section: Introductionmentioning
confidence: 99%